The mirage of the metropolis: city imaging in the age of digital chorography. Issue 1 (2nd January 2018) - Kullmann, Karl
Abstract: Even as cities evolved geographically, the basis of city imaging (as codified by Kevin Lynch) remained relatively stable for over half a century. More recently, digitally driven transformations in urban life challenge the continued relevance of established city-imaging paradigms. Although digital navigation and mapping devices are readily at hand to neutralize any disorienting predicaments, the ability to image cognitively the wider urban environment remains integral to the construction of a meaningful sense of place. Towards the objective of reconciling city imaging with the place-making challenges of the contemporary metropolis, this paper explores the potential for innovating modes of urban mapping and representation. Specifically, the digital re-envisioning of the historical mapping practice of 'chorography' is positioned within Fredric Jameson's challenge for a new aesthetic of cognitive mapping that enables the situational representation of the individual within the vaster totality. In doing so, the paper contributes to the wider adaptation of urban discourse to digitally propelled shifts in urban life.